2003
DOI: 10.1165/rcmb.2002-0109oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Interleukin-10 on Vector-Induced Inflammation and Early Graft Function in Rat Lung Transplantation

Abstract: This study was undertaken to examine the time course of human interleukin (hIL)-10 gene expression after transtracheal administration of adenoviral (Ad)hIL-10 and its effect on the early adenoviral proinflammatory cytokine response and on post-transplant lung function. Using a rat lung transplant model, we observed that lungs retrieved 12 h after the administration of AdhIL-10 were associated with significant improvement in post-transplant lung function. Shorter periods of transfection were associated with sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…This rat model of clinically relevant cold ischemia-reperfusion injury related to lung transplantation was used to further evaluate the role of ELR ϩ CXC chemokines during the pathogenesis of ischemia-reperfusion lung injury (26,27,36,37). This rat model consisted of a cold (i.e., donor lung ischemia time of 6 h at 4 o C) orthotopic single left lung transplantation followed by reperfusion with lung injury evaluated at multiple time points.…”
Section: The Rat Orthotopic Lung Transplantation Model Of Clinically mentioning
confidence: 99%
See 1 more Smart Citation
“…This rat model of clinically relevant cold ischemia-reperfusion injury related to lung transplantation was used to further evaluate the role of ELR ϩ CXC chemokines during the pathogenesis of ischemia-reperfusion lung injury (26,27,36,37). This rat model consisted of a cold (i.e., donor lung ischemia time of 6 h at 4 o C) orthotopic single left lung transplantation followed by reperfusion with lung injury evaluated at multiple time points.…”
Section: The Rat Orthotopic Lung Transplantation Model Of Clinically mentioning
confidence: 99%
“…This rat model consisted of a cold (i.e., donor lung ischemia time of 6 h at 4 o C) orthotopic single left lung transplantation followed by reperfusion with lung injury evaluated at multiple time points. Lewis rats received a lung transplantation from either donor Brown Norway (allograft) or Lewis (isograft) rats as previously described (26,27,36,37). Sham-operated matched controls consisted of a left side thoracotomy with dissection of the pulmonary artery, vein, and left main stem bronchus followed by closure of the chest wall thoracotomy site.…”
Section: The Rat Orthotopic Lung Transplantation Model Of Clinically mentioning
confidence: 99%
“…Primary graft dysfunction (PGD), defined as the occurrence of acute lung injury (ALI) in the allograft within 72 hours of transplantation (1), is a leading cause of death early after lung transplantation (2) and is a risk factor for chronic allograft rejection (3,4). Although PGD is typically attributed to ischemia-reperfusion injury of the allograft, systemic inflammation plays a critical role (5)(6)(7).…”
mentioning
confidence: 99%
“…Furthermore, therapeutic gene transfer can markedly reduce these injuries. Recent experimental evidence (27,31) indicates that gene transfer to the donor prior to harvest, as performed in this study, may be the most feasible method to prevent reperfusion injury in a clinical setting. While donor-directed transfection may not be the optimal strategy to prevent acute allograft rejection, our laboratory has demonstrated the efficacy of this approach, as well as gene transfer to the recipient, in preventing experimental acute rejection (32,33).…”
Section: Discussionmentioning
confidence: 82%
“…As shown in Figure 8 cold preservation used to induce I/R injury was excluded from time after gene transfer as we and others have shown that there is no significant gene expression activity that occurs during cold preservation of lung grafts (8,27). Similarly, as shown in Figure 8, uptake of [ 18 F]FHBG in lungs undergoing acute allograft rejection was comparable to normally transplanted controls.…”
Section: Pet Imaging In Ischemia-reperfusion Injury and Acute Allogramentioning
confidence: 84%